Study on Reasonable Layout of Upper Protective Layer for Prevention Rock Burst under Coal Seam Group with Close Quarters Conditions - Hui-Wu Jin; Zeng-Qiang Yang (Shock and Vibration)
To study the reasonable layout of upper protective layer for the prevention rock burst under coal seam group with close quarters conditions, a panel 3203 that belong to Zhongxing Colliery is taken as a typical engineering background. By means of on-site survey, theoretical analysis, numerical simulation, and on-site industrial applications, the reasonable layout of upper protective layer for prevention rock burst is studied. The results show that the overall stress environment of the floor under gob of upper protective layer is good, and the overall stress environment of the floor under the upper side of gob is also good, but the overall stress environment of the floor under the lower side of gob is bad. According to numerical simulation results, an L-shaped stress superposition area is formed in the lower end of panel 3203 under the original layout scheme conditions, and the maximum stress concentration coefficient is about 2.8 in stage I and 4.0 in stage II. A new stress superposition area is formed at the middle to lower end part of advance mining face of panel 3203 for the stage II under the optimal layout scheme conditions, and the maximum stress concentration coefficient is about 2.4; the original L-shaped stress superposition area is gone due the transfer and release of stress, and the optimal layout scheme has a very significant effect on the prevention and control of the subsequent rock burst accidents; the monitoring results of working resistance of hydraulic supports and surrounding rock deformation indicate that the overall pressure relief of the surrounding rock in advanced segment of 3205 tailgate can be effectively realized. The study conclusions provide theoretical foundation and a new guidance for preventing rock burst with similar engineering geological conditions.